Linear algebra essentials: a workbook for undergraduates - Abd Halim, Suhaila; Yasiran, Siti Salmah; Md Noor, Mohd Rahimie; Mohd Jamil, Nor Hilaliyah; Abdul Hadi, Normi (UiTM Press, 2025)
Linear Algebra Essentials: A Workbook for Undergraduates provides notes, samples of questions and solutions, and tutorials for six chapters. This workbook is designed to support and enhance the understanding of linear algebra fundamentals at the undergraduate level. It also offers a comprehensive approach in solving questions related to linear algebra. In addition, the use of Python is introduced at the end of the book.